Design and Performance of a COVID-19 Hospital Recovery Model. Issue 2 (21st June 2021) - Hu, Michael; Copenhaver, Martin; Langle, Ana Cecilia Zenteno; Koehler, Allison; Daily, Bethany; Levine, Wilton C.; Dunn, Peter F; Safavi, Kyan C.
Abstract : Objective: To determine the accuracy of a predictive model for inpatient occupancy that was implemented at a large New England hospital to aid hospital recovery planning from the COVID-19 surge. Background: During recovery from COVID surges, hospitals must plan for multiple patient populations vying for inpatient capacity, so that they maintain access for emergency department (ED) patients while enabling time-sensitive scheduled procedures to go forward. To guide pandemic recovery planning, we implemented a model to predict hospital occupancy for COVID and non-COVID patients. Methods: At a quaternary care hospital in New England, we included hospitalizations from March 10 to July 12, 2020 and subdivided them into COVID, non-COVID nonscheduled (NCNS), and non-COVID scheduled operating room (OR) hospitalizations. For the recovery period from May 25 to July 12, the model made daily hospital occupancy predictions for each population. The primary outcome was the daily mean absolute percentage error (MAPE) and mean absolute error (MAE) when comparing the predicted versus actual occupancy. Results: There were 444 COVID, 5637 NCNS, and 1218 non-COVID scheduled OR hospitalizations during the recovery period. For all populations, the MAPE and MAE for total occupancy were 2.8% or 22.3 hospitalizations per day; for general care, 2.6% or 17.8 hospitalizations per day; and for intensive care unit, 9.7% or 11.0 hospitalizations per day. Conclusions: The model was accurate in predicting hospital occupancy during the recovery period. Such models may aid hospital recovery planning so that enough capacity is maintained to care for ED hospitalizations while ensuring scheduled procedures can efficiently return. Abstract : Mini-abstracts: To guide hospital recovery planning from COVID-19 surge, we implemented a model to predict inpatient occupancy at our quaternary care hospital. We found that the model could accurately predict future occupancy. Such models can aid recovery planning to ensure capacity for urgent hospitalizations while allowing scheduled procedures to return efficiently.